A Sediment Magnetic Record in the North Pacific Across the Mid-Pleistocene Transition and its Implication on Asian Dust Evolution - Shin, Ji Young; Hyeong, Kiseong; Kim, Wonnyon (Frontiers in Earth Science, 2021)
Eolian dust deposited in the North Pacific is an important archive of the evolutionary history of Asian interior source regions and climate system. Here, we present a ∼1 Myr sediment magnetic record from the central North Pacific to characterize eolian dust properties since the middle Pleistocene. For the studied sediments, magnetic components are mainly identified as biogenic magnetite and detrital magnetic minerals (dust and volcanic origins) based on coercivity analysis, microscopic observations, and sedimentological information. The detrital magnetic component is characterized by high coercivity (>100 mT) and shows a long-term increase in concentration since ∼1 Ma. In particular, the concentration shows a considerable increase at ∼0.8–0.7 Ma compared to the inorganic silicate fraction, indicative of magnetic mineral enrichment in detrital sediment fraction. At the same time, the coercivity distribution of the detrital component also decreases, which can be attributed to an increase in the ferrimagnetic mineral contribution. As the detrital sediments are primarily wind-blown particles, such ferrimagnetic enrichment implies a change in dust source materials after ∼0.8 Ma, which could be explained by the reorganization of atmospheric circulation and/or regional aridification in source regions across the mid-Pleistocene transition. The dust property change in source areas is likely to be synchronized across the North Pacific based on the similarity of the long-term trend of magnetic signals.